PENINGKATAN MOTIVASI PEREMPUAN PADA KEGIATAN PEMBERDAYAAN ONLINE SHOP DI DESA PASIRBATANG - Novaryansyah, Givan; Hakim, Jihan Zahrah Rahmatilah; Shadrina, Risty Ramadhani Nur; Az-Zahra , Ajeng Arfah; Amelia, Martina; Nurlaila, Nurlaila (Jurnal Pengabdian Masyarakat Indonesia, 2024)
In a series of services entitled "Increasing Women's Motivation in Online Shop Empowerment Activities in Pasir Batang Village" aims to examine the influence of women's motivation on online shop empowerment activities in Pasirbatang village. In this research, women's motivation is considered an important factor that influences the success of online shop empowerment activities. in Pasir Batang village. By understanding the influence of women's motivation, we can provide recommendations to sustainability stakeholders and the government to increase online shop empowerment activities in Pasirbatang village.